Urban poachers: Cosplay, playful cultures and the appropriation of urban space. (1st September 2018) - Crawford, Garry; Hancock, David
This article considers cosplayers' use and transformation of urban space. Cosplay provides an important subcultural embodiment of contemporary popular culture, through which we can learn a great deal about contemporary forms of fandom, participatory culture and (mostly notably here) urban appropriation. This article draws on data gathered from a four-year ethnographic study, which includes the use of art as a method, but here specifically looks at a small cosplay community that regularly meets in a park in Manchester. The article argues that a useful way of understanding cosplay is to consider the relationship between play and culture. In particular, the article sets out a consideration of how cosplayers transform social spaces through the use of process of synecdoche and asyndeton, which link together and edit out parts of the built environment – or what we term 'urban poaching'.